(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: Catheter-associated urinary tract infection (CAUTI) is one of the problems affecting the outcome and quality of treatment for patients in intensive care units, this study was conducted to describe the current status of catheter-associated urinary tract infection. Method: Cross-sectional descriptive study on patients with catheters placed at the intensive care department of national geriatric hospital from July 2024 to October 2024. Results: 138 patients were involved in this study in which the male/female ratio was 1.5/1, the common age was 60 – 75 was 57,2%, the CAUTI rate was 31.68%, the rate of urinary tract infection at the time of admission was 26.8%, the rate of CAUTI was 31.68%, the frequency was 34.2 cases/1000 days of catheter retention. The longer the catheter is in place, the higher the rate of CAUTI. The rate of CAUTI with catheter in place for more than 5 days is 39%, and for more than 8 days is 42.4% at 8 days, with an OR of 5.71 with p < 0.05. Common paraclinical symptoms of CAUTI are leukocytes in urine (+) in 50% and positive urinary nitrite in 62.5%. Conclusion: Catheter-associated urinary tract infection (CAUTI) is a common disease in the Emergency Department of the Central Geriatric Hospital with a rate of 31.68%, a frequency of 34.2 cases/1000 days of catheter in place. Optimizing catheter placement time is the key to limiting CAUTI.